Protecting the memory of objects from nostalgia - Borges, Afonso (2019)
In Das gewöhnliches, Bazon Brock features vulgar objects, inexpensive things used in our everyday lives. Such as Pompey’s artifacts were pivotal to understand life after a historical loss, so do normal objects, our tangible legacy, and our connection with them may very well be what defines our humanity. They not only represent but are also as much cause as they are the consequence of the way we live, contributing to the definition of that lifestyle and thus becoming essential in enhancing social values. Every object has a meaning beyond its materiality, and the shape envisioned by its project promotes a reflection about the way we subsist, depends on our habits, suggests how we can live both individually and collectively, and encompasses a political vision or a rejection of the social organization. Design’s participation in social construction becomes particularly acute in a time that so easily displays the erosion of ethical values, escalatingthedevaluation of truth,theinstitutionalizationof hate speech, and the increasing assemblage of walls. Although history may not repeat itself exactly in the same manner, the warnings should not be ignored, and Design must not withdraw from action. The role of Design in this crossroad becomes particularly emphasized in association with concepts such as memory. If Design’s tolerance is not questioned when considering the respect for culture, the defense of collective knowledge by designers, the familiarity with products with which we have lived throughout generations, it may also become permeable because of that retrospective. Memory seems to entail an inevitable sense of place. When our projects envision evolution but remain a reference to what we know, reminding us of our ancestors’ homes through recognition and emotional value, those objects will inevitably distinguish themselves from others. It is necessary to protect that memory, but the homage to what is local and national is precisely what may become the source of the rhetorical foundation which helps to sustain nationalist discourses. Therefore, the distinction between the notion of memory within Design and ideas such as nostalgia and selective memory becomes imperative, since those are the concepts which may truly feed intolerance. Nevertheless, it is also crucial to demonstrate Design’s intercultural nature, its openness, as well as its contribution to the obliteration of borders and to the absence of possible conflicts between an international perspective and the (conscious or unconscious) resource to the past and to our shared inherited knowledge.